2021
DOI: 10.3390/biomedicines9020121
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13C Spectroscopy with Simple Slice-and-Frequency-Selective Excitation

Abstract: Hyperpolarized 13C nuclear magnetic resonance spectroscopy can characterize in vivo tissue metabolism, including preclinical models of cancer and inflammatory disease. Broad bandwidth radiofrequency excitation is often paired with free induction decay readout for spectral separation, but quantification of low-signal downstream metabolites using this method can be impeded by spectral peak overlap or when frequency separation of the detected peaks exceeds the excitation bandwidth. In this work, alternating frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…This illustrates that the metabolic interpretations of k pl needs to be complemented with further metabolic and clinical parameters, for example metabolite levels in plasma from the patient, which may be affected by fasting or a metabolic syndrome. Moreover, to obtain more specific information on the metabolic status of the analyzed tissue for (not only) tumor diagnosis and therapeutic monitoring, the potentials of metabolic imaging using hyperpolarized 13 C-pyruvate could be enhanced by also using other hyperpolarized 13 C-metabolites of energy metabolism; these could include, for example, 13 C-fumarate [ 7 ], 13 C-lactate [ 73 ], or co-polarization of 13 C-pyruvate with 13 C-fumarate [ 74 ] or 13 C-urea [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that the metabolic interpretations of k pl needs to be complemented with further metabolic and clinical parameters, for example metabolite levels in plasma from the patient, which may be affected by fasting or a metabolic syndrome. Moreover, to obtain more specific information on the metabolic status of the analyzed tissue for (not only) tumor diagnosis and therapeutic monitoring, the potentials of metabolic imaging using hyperpolarized 13 C-pyruvate could be enhanced by also using other hyperpolarized 13 C-metabolites of energy metabolism; these could include, for example, 13 C-fumarate [ 7 ], 13 C-lactate [ 73 ], or co-polarization of 13 C-pyruvate with 13 C-fumarate [ 74 ] or 13 C-urea [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…While hyperpolarized imaging is feasible and several groups have demonstrated myocardial hyperpolarized imaging, capable of identifying focal changes, 24,34,35 including with DCA, previous imaging experiments have demonstrated that these changes are homogeneous 36 . Therefore, we performed slice‐selective spectroscopy as a more robust, efficient, and appropriate technique for this study, as has been repeatedly used previously 37–39 . Finally, while intracellular pH (pH i ) can be derived from the H 13 CO 3 − / 13 CO 2 ratio, 40 the 13 CO 2 signal was below the detection level for this experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…36 Therefore, we performed slice-selective spectroscopy as a more robust, efficient, and appropriate technique for this study, as has been repeatedly used previously. [37][38][39] Finally, while intracellular pH (pH i ) can be derived from the H 13 CO 3 À / 13 CO 2 ratio, 40 the 13 CO 2 signal was below the detection level for this experimental setup. This precludes the direct investigation of a pH i change; if DCA reduced pH i then the estimated effects of treatment on bicarbonate would have been underestimated.…”
mentioning
confidence: 84%
“…For HP measurements, a thermally polarized [1‐ 13 C]lactate phantom (approx. 300 μL, 2.2 M, 1 mM Dotarem) was placed adjacent to the animal for frequency calibration and power adjustments 24 . The imaging setup was as described above for the in vitro imaging experiment, with a shim volume over the abdomen.…”
Section: Methodsmentioning
confidence: 99%
“…300 μL, 2.2 M, 1 mM Dotarem) was placed adjacent to the animal for frequency calibration and power adjustments. 24 The imaging setup was as described above for the in vitro imaging experiment, with a shim volume over the abdomen. Subjects were imaged twice within the same session, 1 h apart, with the same 3D bSSFP sequence as described above, except: (1) repetitions were acquired instead of averaged;…”
Section: In Vivo Imagingmentioning
confidence: 99%